Ethno-Apophasis: An Ethnographic Theology of Thinness and Refusal - Chi, Elisha (2023)
The critical onboarding of ethnography evinced by scholars in theology, religious studies and Christian ethics compellingly generates ecclesiologies and other theologies inclusive of non-academic life. Yet, in a critical reflection on methodologies in ecclesiological research, this paper questions the growing predominance of ethnography, specifically ethnographic thickness. Drawing upon the work of anthropologist Audra Simpson, this paper argues that the ethnographic turn in religious ethics and theology and religious studies misses (at best) or ignores (at worst) the epistemological violence lurking at the root of this method. By looking into practices of ethnographic thinness and refusal, this paper highlights apophasis as the best theological grounding for scholars engaging with ethnography. Ethnographic apophasis requires practitioners to heed the colonial and settler colonial realities inherent in the method of ethnography itself; ethically pushing notions of solidarity into anticolonial practice.
Keywords: Religious Ethics; Religious Transformation; Practical Theology; thick description; Ethnography; Theological Anthropology; colonialism and neo-colonialism